Finnish Preschool and First-Grade Children's Use of Media at Home - Korkeamäki, Riitta; Dreher, Mariam; Pekkarinen, Asko (Human Technology, 2012)
We investigated Finnish children's use of print and electronic media in the home and their literacy development. Questionnaire data from 857 parents of preschoolers (collected in 2006 and 2007) and first graders (2008) showed that homes were well equipped with electronic media including Internet access in almost every home, although only a third of the children used the Internet. Television, print media, and videos/DVDs were more commonly used than computers. Most first graders but few preschoolers had mobile phones. Most parents read bedtime stories, had a sizable number of children's books, and library visits were common. Boys' and girls' skills in reading did not differ at the beginning of their preschool year. But girls showed more interest in writing while boys played more console and computer-based games. Most first graders were reading early in the school year, suggesting that electronic media are not harmful but may even support literacy development.